DIAGNOSTIC ACCURACY OF PROCALCITONIN FOR DIAGNOSING NEONATAL SEPSIS KEEPING BLOOD CULTURE AS GOLD STANDARD (The Research of Medical Science Review, 2025)
Background: Neonatal infections contribute to third most common cause of neonatal deaths in developing parts of the world. This study was planned to determine diagnostic accuracy of procalcitonin for diagnosing neonatal sepsis taking blood culture as gold standard.Subjects and Methods: This cross-sectional validation study was performed at the Pediatric Medicine Department of The Children’s Hospital and Institute of Child Health Multan, from 17th February 2024 to 16th August 2024. Consecutive 195 neonates of either gender presenting with suspected sepsis were enrolled after parental informed consent. Probable neonatal sepsis was defined by positivity in at least 2/5 criteria: low total leukocyte count, low absolute neutrophil count, an immature-to-total neutrophil ratio ≥0.2, elevated ESR, or raised C-reactive protein. Confirmed sepsis required isolation of a pathogenic organism from blood, urine, or cerebrospinal fluid as definitive evidence. Serum procalcitonin was measured by immunoluminometry and cut off levels for sepsis were set at ≥0.5 ng/ml. Diagnostic accuracy of procalcitonin is calculated against probable and culture confirmed neonatal sepsis. Results: Median neonatal age was 13 days, with 56.9% being male. Probable sepsis was diagnosed in 64.1% of cases, while 54.9% were confirmed by culture. Serum procalcitonin demonstrated moderate sensitivity (57.6%, 51.4%) paired with high specificity (98.6%, 79.6%) and an excellent positive predictive value (98.6%, 75.3%) for probable and confirmed neonatal sepsis respectively.Conclusion: Although a serum procalcitonin level of ≥0.5 ng/mL is highly specific for neonatal sepsis, its limited sensitivity indicates that additional diagnostic markers are necessary for early detection and optimal clinical management.